2017
DOI: 10.1007/s13534-017-0036-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-time biofeedback device for gait rehabilitation of post-stroke patients

Abstract: In this work, we develop a device, called 'Walk-Even', that can provide real-time feedback to correct gait asymmetry commonly exhibited in post-stroke survivors and persons with certain neurological disorders. The device computes gait parameters, including gait time, swing time, and stance time of each leg, to detect gait asymmetry and provide corresponding real-time biofeedback by means of auditory and electrotactile stimulation to actively correct the user's gait. The system consists of customized forcesenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…They found that the average number of sessions (2 hours per session) for walking and developing sit-stand transitions with contact guard assistance (i.e., helper maintains touch or near-touch contact, but provides no assistance) and close supervision were 15 and 18 sessions, respectively. In this regard, there are few studies that showed that the use of biofeedback could accelerate the learning process and reduce the time and effort devoted to learn how to use an exoskeleton [101][102][103][104].…”
Section: Protocol Designmentioning
confidence: 99%
“…They found that the average number of sessions (2 hours per session) for walking and developing sit-stand transitions with contact guard assistance (i.e., helper maintains touch or near-touch contact, but provides no assistance) and close supervision were 15 and 18 sessions, respectively. In this regard, there are few studies that showed that the use of biofeedback could accelerate the learning process and reduce the time and effort devoted to learn how to use an exoskeleton [101][102][103][104].…”
Section: Protocol Designmentioning
confidence: 99%
“…During the study, patients who could no longer participate in the intervention program due to change of medical state, who had less than 80% participation rate were excluded. The patients and the assessing therapist were blinded to the group allocation [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ma and his colleagues revealed the tactile feedback can be used for the gait symmetry [ 19 ]. We also observed the auditory feedback can be effective to achieve gait symmetry for stroke patients [ 21 ]. Our previous study applied auditory feedback with pneumatic-pressure insole to chronic stroke survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Research investigating electrotactile feedback on the lower limb in closed‐loop systems intended for other application scenarios was also mostly directed toward single‐channel systems 17,18 . Multi‐channel feedback interfaces are superior to single‐channel systems in terms of usability, setup, donning, and doffing time 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Research investigating electrotactile feedback on the lower limb in closed-loop systems intended for other application scenarios was also mostly directed toward single-channel systems. 17,18 Multi-channel feedback interfaces are superior to single-channel systems in terms of usability, setup, donning, and doffing time. 19,20 The requirement for the use of tactile feedback with state-of-the art robotic hands in transmitting high bandwidth information or even multimodal information to the user.…”
Section: Introductionmentioning
confidence: 99%